A comparison of plasmid DNA delivery efficiency and cytotoxicity of two cationic diblock polyoxazoline copolymers. (3rd April 2017) - Lehner, Roman; Liu, Kegang; Wang, Xueya; Wolf, Marc; Hunziker, Patrick
Abstract: Cationic polymers as non-viral gene delivery carriers are widely used because of their strong condensing properties and long-term safety, but acute cytotoxicity is a persistent challenge. In this study, two types of polyplexes were prepared by co-formulating plasmid DNA and two cationic diblock copolymers PABOXA5 -b-PMOXA33 -PA (primary amine) and PABOXA5 -b-PMOXA33 -TA (tertiary amine) to check their transfection efficacies in HeLa cells and HEK293T cells, respectively. The plasmid DNA/PABOXA5 -b-PMOXA33 -PA polyplex showed higher transfection efficacy compared to the plasmid DNA/PABOXA5 -b-PMOXA33 -TA polyplex under an N/P ratio of 40. Both polymers exhibited low toxicity, attributed to the shielding effect of a hydrophilic, noncharged block. Mechanistic insight into differential transfection efficiencies of the polymers were gained by visualization and comparison of the condensates via transmission electron and atomic force microscopy. The results provide information suited for further structure optimization of polymers that are aimed for targeted gene delivery.